Higher education teaching and learning assessment: an e-guidebook for film concept design with artificial intelligence / Khong Kok Wai, Norlela Ismail and Mohd. Suhaimi Juhan - Khong, Kok Wai; Ismail, Norlela; Juhan, Mohd. Suhaimi (2024)
Recognising students' challenges in grasping complex film design principles and maintaining enthusiasm, this project proposes an e-guidebook harnessing AI to streamline assignment preparation and offer personalised guidance. It focuses on promoting AI to enhance students' comprehension, creativity, and engagement in film concept design assignments in the institution of higher education. The methodology involves a comprehensive literature review, employing AI-powered tools, and rigorous testing to ensure the e-guidebook's effectiveness and relevance. Anticipated results include increased student engagement, improved understanding of film design principles, and enhanced creativity in assignment submissions. The discussion explores the transformative impact of AI on education, addressing ethical considerations and the role of educators in guiding responsible AI use. In conclusion, this project signifies the potential of AI to revolutionise education, fostering a more enriching and effective learning experience that empowers students and shapes the future of teaching and learning.